Dynamics of Palladium on Nanocarbon in the Direct Synthesis of H2O2. Issue 1 (16th October 2013) - Arrigo, Rosa; Schuster, Manfred E.; Abate, Salvatore; Wrabetz, Sabine; Amakawa, Kazuhiko; Teschner, Detre; Freni, Maria; Centi, Gabriele; Perathoner, Siglinda; Hävecker, Michael; Schlögl, Robert
Abstract This work aims to clarify the nanostructural transformation accompanying the loss of activity and selectivity for the hydrogen peroxide synthesis of palladium and gold–palladium nanoparticles supported on N‐functionalized carbon nanotubes. High‐resolution X‐ray photoemission spectroscopy (XPS) allows the discrimination of metallic palladium, electronically modified metallic palladium hosting impurities, and cationic palladium. This is paralleled by the morphological heterogeneity observed by high‐resolution TEM, in which nanoparticles with an average size of 2 nm coexisted with very small palladium clusters. The morphological distribution of palladium is modified after reaction through sintering and dissolution/redeposition pathways. The loss of selectivity is correlated to the extent to which these processes occur as a result of the instability of the particle at the carbon surface. We assign beneficial activity in the selective hydrogenation of oxygen to palladium clusters with a modified electronic structure compared with palladium metal or palladium oxides. These beneficial species are formed and stabilized on carbons modified with nitrogen atoms in substitutional positions. The formation of larger metallic palladium particles not only reduces the number of active sites for the synthesis, but also enhances the activity for deep hydrogenation to water. The structural instability of the active species is thus detrimental in a dual way. Minimizing the chance of sintering of palladium clusters by all means is thus the key to better performing catalysts.